Identifikasi Senyawa Aktif Antibakteri dari Ekstrak Bajakah (Spatholobus Littoralisk Hask) dengan GCMS (Gass Chromatography Mass Spectroscopy): Identification of Active Antibacterial Compounds from Spatholobus Littoralisk Hask Extract With GCMS (Gass Chromatography Mass Spectroscopy) - Kunti Nastiti; Dyan Fitri Nugraha; Darini Kurniawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Bajakah wood (Spatholobus Littoralisk Hask) is empirically used by the community to treat stomach pain, diarrhea and is even believed to be able to treat cancer. Several studies have shown its activity as an antibacterial. The purpose of this study was to identify compounds with antibacterial properties using Gas Chromatography Mass Spectroscopy (GCMS). The method used in this research is the experimental method. Bajakah plants were obtained from seven different areas, then extracted and fractionated. The fraction identified in this study was the n-hexan fraction. Preliminary tests were carried out using thin layer chromatography (TLC) bioautography for compounds that have the potential as antibacterial. Compounds in the n-Hexan fraction were further identified using Gass Chromatography Mass Spectroscopy (GCMS). The results showed Bajakah wood from seven regions had antibacterial activity seen from the formation of inhibition zones on compound spots on TLC that had been planted in agar media. There are 23 types of compounds identified by GCMS in this n-hexan fraction. In this study, the dominant compound seen from the largest area was Stigmast-5-en-3-ol, (3.beta.,24S)- (CAS) Clionaster (26.74%). The results of TLC bioautography of the n-Hexan fraction showed antibacterial activity and the dominant compound was Stigmast-5-en-3-ol, (3.beta.,24S)- (CAS) Clionaster.